Loss of progesterone receptor membrane component 1 promotes hepatic steatosis via the induced de novo lipogenesis - Sang R. Lee (Nature Portfolio, 2018)
Abstract Non-alcoholic fatty liver disease (NAFLD) results from triglyceride accumulation within the liver and some of them advances to non-alcoholic steatohepatitis (NASH). It is important to note that in NAFLD development, hepatic de novo lipogenesis (DNL) derives from excess carbohydrates and fats under a condition of excess energy through β-oxidation. As a main regulator for DNL, sterol regulatory element-binding protein 1 (Srebp-1) forms complex with progesterone receptor membrane component 1 (Pgrmc1). To investigate whether Pgrmc1 may have a notable effect on DNL via SREBP-1 activation, we generated Pgrmc1 knockout (KO) mice and fed a high fat diet for one month. High-fat-fed Pgrmc1 KO mice showed a substantial increase in levels of hepatic TG accumulation, and they were predisposed to NAFLD when compared to WT mice. Loss of Pgrmc1 increased mature SREBP-1 protein level, suggesting that induction of hepatic steatosis in Pgrmc1 KO mice might be triggered by de novo lipogenesis. Moreover, Pgrmc1 KO mice were also more vulnerable to early stage of NASH, showing high levels of alanine aminotransferase, obesity-linked pro-inflammatory cytokines, and fibrosis markers. This is interesting because Pgrmc1 involves with the first step in regulating the hepatic de novo lipogenesis under an excess energy condition.